Expanding the phenotype of UPF3B-related disorder: Case reports and literature review - Romano, Ferruccio (John Wiley & Sons, 2025)
UPF3B encodes the Regulator of nonsense transcripts 3B protein, a core-member of the nonsense-mediated mRNA decay pathway, protecting the cells from the potentially deleterious actions of transcripts with premature termination codons. Hemizygous variants in the UPF3B gene cause a spectrum of neuropsychiatric issues including intellectual disability, autism spectrum disorder, attention deficit hyperactivity disorder, and schizophrenia/childhood-onset schizophrenia (COS). The number of patients reported to date is very limited, often lacking an extensive phenotypical and neuroradiological description of this ultra-rare syndrome. Here we report three subjects harboring UPF3B variants, presenting with variable clinical pictures, including cognitive impairment, central hypotonia, and syndromic features. Patients 1 and 2 harbored novel UPF3B variants-the p.(Lys207{*}) and p.(Asp429Serfs{*}27) ones, respectively-while the p.(Arg225Lysfs{*}229) variant, identified in Patient 3, was already reported in the literature. Novel features in our patients are represented by microcephaly, midface hypoplasia, and brain malformations. Then, we reviewed pertinent literature and compared previously reported subjects to our cases, providing possible insights into genotype-phenotype correlations in this emerging condition. Overall, the detailed phenotypic description of three patients carrying UPF3B variants is useful not only to expand the genotypic and phenotypic spectrum of UPF3B-related disorders, but also to ameliorate the clinical management of affected individuals.